The MULTI Process Challenge - Almeida, Joao Paulo A.; Rutle, Adrian; Wimmer, Manuel; Kuhne, Thomas (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
This challenge is intended to allow submitters to demonstrate the use of multi-level modeling techniques and enable the comparison of submissions and hence framework/language capabilities. The multi-level modeling community is invited to respond to this challenge with papers describing solutions to the challenge. Authors should emphasize the merits of their solutions according to the aspects defined in this challenge description. The challenge follows up on the "MULTI Bicycle Challenge" which was used in MULTI 2017 and MULTI 2018, and reuses some criteria that were established in these previous editions. Despite the similar criteria, the subject domain has been changed entirely and new criteria have been added which are intended to increase opportunities for languages and tools to exercise their capabilities.